The Raw Material Inventory Accounting Information System Analysis: Analisis Sistem Informasi Akuntansi Persediaan Bahan Baku - Intan Nur Lailiyah; Santi Rahma Dewi (Academia Open, 2021)
The aims of this research are to describe the Accounting Information System for raw material inventory at PT. Perdana Sukses Makmur and to analyze the Accountingi Information iSystem for raw material inventory is accordance to the theory of Accounting iInformation System. This research used qualitative approach. Descriptive method is used in this research. To collect the data, this research used interview, documentation and observation. Interview method is used to find in-depth information from company staff and academic experts by giving questions. Documentation method is used to support and strengthen the data in this study. Observation method is used to record the information and activities that occur during field research. The data ianalysis techniquesi used iin this istudy were datai reduction, idata idisplay and iconclusion idrawing/data iverification. Thei results of ithis study ishowed that Accounting iInformation System for raw material inventory are running well at PT. Perdana Sukses Makmur even though it’s still manual. It supported by the implementation of procedures that related to the supply of raw materials by involving various functions with their respective duties and responsibilities and is equipped with the documents that can be accounted for.